The Effect of Cow’s Milk Substitution with Soybean’s Milk and The Concentration Rate of Ananas comosus Extract Addition to Cottage cheese Physical and Chemical Quality - Firman Jaya; Didik Kusumahadi (Faculty of Animal Science Universitas Brawijaya, 2009)
The objective of current study was to find out effect of cow’s milk substitution with soybean’s milk and the concentration rate of Ananas comosus extract addition to produce cottage cheese. The results of Ananas comosus addition and milk proportion showed that the highest protein content, moisture content, rendement were 12.773% , 85.775%, 4,748 and 15.773, respectively. While the L (lightness) value, a (redness) and b (yellowness) were 12.773, 12.773 and 22.648, respectively. Keywords : cow’s milk, soybean’s milk, Ananas comosus, cottage cheese